SAT0618 Disturbances of the acral perfusion detected by fluorescence optical imaging are associated with the development of ischemic complications in patients with systemic sclerosis. (15th June 2017) - Lüders, S; Friedrich, S; Ohrndorf, S; Werner, S; Burmester, G-R; Riemekasten, G; Backhaus, M
Abstract : Background: Systemic sclerosis (SSc) is a condition causing an impaired microcirculation with the risk of ischemic complications such as digital ulcers and pitting scars (DU/PS). Fluorescence optical imaging (FOI) is an imaging method that detects enhanced microcirculation as a sign of joint inflammation in both hands of patients with rheumatoid arthritis and other arthritides [1, 2]. FOI's impact to record disturbed microcirculation in the hands of patients with systemic sclerosis has not yet been sufficiently investigated. Objectives: To find associations of disturbed microcirculation initially detected by FOI and the development of new DU/PS throughout a follow-up of 12 months. Methods: Sixty-three patients with SSc were included and received FOI examination following the Xiralite-System guidelines (ICG 0.1mg/kg BW i.v.; 6 minute duration) as well as capillaroscopy at baseline. After a mean follow-up time of 12 months (min-max: 8–20 months), all participants were followed regarding the development of new ulcers and pitting scars. Results: A disruption of microcirculation in FOI was defined as a lack of a sufficient fluorescent signal in at least one fingertip over the entire course of the examination and was found in 11 of 63 SSc patients. All patients had a history of DU/PS and frequently presented with a late pattern capillaroscopy (9 out of 11) at baseline. Fingers with a disrupted microcirculation also showed a reduced capillary density to a greater extend (96.0%) than fingers with a sufficient signal in FOI (76.0%; p=0.0241). 30 of 60 patients developed digital ulcers or pitting scars during follow up (3 drop outs due to death (n=2) or withdrawal). 81.8% of patients with a disturbed microcirculation in FOI developed these complications during follow-up compared with 42.9% of patients without a disruption in FOI (p=0.0419; OR=6.0 [95% CI 1.2 - 30.7]). A disruption of microcirculation especially increased the risk of developing DU/PS in the same finger: 20.1% of fingers with normal, but 65.4% with a missing FOI signal in the fingertip presented with an ischemic complication during follow-up (p<0.0001; OR=7.5 [95% CI 3.3 - 17.3]). Conclusions: Fluorescence optical imaging can reveal an impaired microcirculation in patients with systemic sclerosis, which is associated with microangiopathic changes as seen in capillaroscopy as well as the subsequent development of digital ulcers and pitting scars. Therefore, FOI might help to identify patients at risk for these complications. References: Werner SG et al. Inflammation assessment in patients with arthritis using a novel in vivo fluorescence optical imaging technology. Ann Rheum Dis. 2012 Apr;71(4):504–10. Werner SG et al. Indocyanine green-enhanced fluorescence optical imaging in patients with early and very early arthritis: a comparative study with magnetic resonance imaging. Arthritis Rheum. 2013 Dec;65(12):3036–44. Acknowledgements: . We thank Gabriela Schmittat for technical and Dr. Bernd Schicke, PhD, for statistical assistance. Disclosure of Interest: None declared